Cloudy With A Chance of Meatballs - Barrett, Judi (New York, New York : Simon & Schuster for Children, 1978)
Life is delicious in the town of Chewandswallow where it rains soup and juice, snows mashed potatoes and storms hamburgers. Life in the town was delicious until the weather took a turn for the worse.
3.6
4-8